PENGARUH FASHION INVOLVEMENT DAN FOMO TERHADAP IMPULSIF BUYING PRODUK THRIFTING (Studi kasus pada Gen Z di Yogyakarta) - Prasa Risky Dermawan; Yunita Fitri Wahyuningtyas (Politeknik Negeri Jakarta, 2025)
This study aims to analyze the effect of fashion involvement and FOMO on impulsive buying of thrifting products among Generation Z in Yogyakarta. The sample consists of 100 respondents aged 13 to 28 who have purchased thrifting products. Data were collected using an online questionnaire. The results show that fashion involvement has no significant effect on impulsive buying, indicating that although Generation Z is interested in fashion, their involvement does not always influence impulsive purchasing behavior. On the other hand, FOMO has a significant positive effect on impulsive buying, where the higher the anxiety of missing out on trends, the greater the tendency to make impulsive purchases. These findings emphasize that FOMO plays a more dominant role in influencing impulsive buying decisions of thrifting products among Generation Z. Keywords: Fashion Involvement, FOMO, Impulsive Buying, Thrifting, Generation Z